A linear programming approach to limited angle 3D recostruction from DSA projections - Weber, Stefan; Schüle, Thomas; Schnörr, Christoph; Hornegger, Joachim (Methods of Information in Medicine, 2004)
Objectives: We investigate the feasibility of binary-valued 3D tomographic reconstruction using only a small number of projections acquired over a limited range of angles. Methods: Regularization of this strongly ill-posed problem is achieved by (i) confining the reconstruction to binary vessel/non-vessel decisions, and (ii) by minimizing a global functional involving a smoothness prior. Results: Our approach successfully reconstructs volumetric vessel structures from three projections taken within 90°. The percentage of reconstructed voxels differing from ground truth is below 1%. Conclusion: We demonstrate that for particular applications - like Digital Subtraction Angiography - 3D reconstructions are possible where conventional methods must fail, due to a severely limited imaging geometry. This could play an important role for dose reduction and 3D reconstruction using non-conventional technical setups.
UnivIS-Import:2015-03-09:Pub.2004.tech.IMMD.IMMD5.alinea